Pengaruh Jiwa Kewirausahaan dan Inovasi terhadap Keberhasilan Usaha - Dea Putri Amanda; Zuhrinal M. Nawawi (ManBiz: Journal of Management and Business, 2023)
This study aims to determine the effect of the entrepreneurial spirit and innovation on business success. Entrepreneurship is great if business progress is enhanced by changing attitudes, such as being more proactive and responsive in creating opportunities and creating new products that are not available in the market, thus becoming a market leader. Entrepreneurship is the ability to be creative and innovative, keen to see opportunities, and always open to any input and positive changes that can lead to sustainable business growth. Entrepreneurs who are strong enough are needed to improve the economy of a country. Entrepreneurs must be able to compete and always be able to increase their productivity. One way is to have an entrepreneurial and innovative spirit. This research method uses qualitative research. The results of the study prove that the entrepreneurial spirit and innovation have a positive and significant influence on business success. Keywords: Entrepreneurship Spirit, Innovation, Success Of Businnes.